Tenon's capsule granuloma at the donor site after conjunctival grafting: short report - Gus,Patrícia Ioschpe (2003)
PURPOSE: To describe a rare complication at the donor site of conjunctival transplantation. METHODS: The authors report the clinical, surgical, postoperative and histologic aspects of a Tenon's granuloma that followed an uneventful pterygium excision with conjunctival transplantation. RESULTS: Histology identified an hemangiomatous-like structure with some areas of foreign body granuloma overlying necrotic epithelial cels, easily excised surgically. CONCLUSIONS: Pyogenic granuloma is an inadequate term to describe an inflammatory nonsuppurative reaction that may follow uneventful conjunctival surgery in susceptible individuals.